Henry James and the queerness of style - Ohi, Kevin, 1972- (University of Minnesota Press, 2011)
This study begins with the proposition that to read Henry James - particularly the late texts - is to confront the queer potential of style and the traces it leaves on the literary life. In contrast to other recent analyses, this book asserts that James's queerness is to be found neither in the homoerotic thematics of the texts, however startlingly explicit, nor in the suggestions of same-sex desire in the author's biography, however undeniable, but in his style. There are many elements in the style that make James's writing queer. But if there is a thematic marker, the book shows, it is belatedness.